Depth extension and sidelobe suppression in optical coherence tomography using pupil filters - Gu, Jun (2015)
We demonstrate a new focus engineering scheme to achieve both extended depth of focus (DOF) and sidelobe suppression in spectral-domain optical coherence tomography (SD-OCT) system. Each of the illumination pupil function and the detection pupil function is modulated using an annular pupil filter implemented by center obscuration. The two pupil filters are arranged in a dark-field configuration such that the first sidelobe of the illumination point-spread function (PSF) matches the first minimum of the detection PSF in the lateral focal plane. We tested the feasibility of the proposed scheme numerically, and then constructed a dark-field OCT (DF-OCT) system to further verify its effectiveness experimentally. Simulation results show that a DOF gain of 4.2 can be achieved compared with a full aperture OCT (FA-OCT) system, with a suppression ratio of 2.9 dB for the first sidelobe compared with an annular-aperture bright-field OCT (BF-OCT) system. Experimental results show that the constructed DF-OCT extends the DOF by three-fold compared with the constructed FA-OCT, and suppresses the first sidelobe by 3.1 dB compared with the BF-OCT. The penalty for the extended DOF is an ~11.6 dB drop in sensitivity compared with the FA-OCT system.